Health Information Seeking Behaviors of Ethnically Diverse Adolescents - Okoniewski, Anastasia E. (2014)
Research on health information has primarily focused on the needs of adults or parents of children with chronic illnesses or consumers. There is limited research on the health information needs of adolescents and in particular those from underserved communities. The primary objective of this qualitative study was to understand the health information needs of healthy, urban adolescents, and how they met those needs. Focus group methodology was used to gather information from a sample of ethnically diverse urban adolescents. Data was analyzed using Kriekelas’ Information Seeking Behavior framework to, examine the participants” report of their immediate and deferred health information needs. Our sample of adolescents used several different sources to satisfy their health information needs depending on acuity and severity, which was congruent with Kriekelas’ framework. Understanding how adolescents use technology to meet their health information needs, and in what order of preference, will be critical for the development of technology that adolescents find useful and has the potential to decrease health disparities.